2021
DOI: 10.1111/ina.12825
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bacterial and fungal communities in indoor and outdoor air of elementary school classrooms by 16S rRNA gene and ITS region sequencing

Abstract: The advent of high‐throughput sequencing methods allowed researchers to fully characterize microbial community in environmental samples, which is crucial to better understand their health effects upon exposures. In our study, we investigated bacterial and fungal community in indoor and outdoor air of nine classrooms in three elementary schools in Seoul, Korea. The extracted bacterial 16S rRNA gene and fungal ITS regions were sequenced, and their taxa were identified. Quantitative polymerase chain reaction for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 56 publications
4
27
0
Order By: Relevance
“…Several studies have shown that the primary sources of bacterial communities in indoor air were human occupants, pets, plants, water, plumbing systems, heating, ventilation, air-conditioning systems, and the outdoor environment [26,27]. We obtained similar results in this study (Table 1), where several DGGE bands were considered to be derived from the human oral cavity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies have shown that the primary sources of bacterial communities in indoor air were human occupants, pets, plants, water, plumbing systems, heating, ventilation, air-conditioning systems, and the outdoor environment [26,27]. We obtained similar results in this study (Table 1), where several DGGE bands were considered to be derived from the human oral cavity.…”
Section: Discussionsupporting
confidence: 81%
“…Enhydrobacter, Streptococcus, and Micrococcus were the top three most abundant genera in indoor air (elementary school classrooms). At the same time, Methylobacterium, Pseudomonas, and Deinococcus were the top three most abundant genera in outdoor air [26]. Macrococcus, Micrococcus, and Staphylococcus were dominant in indoor air (office rooms) [37,38].…”
Section: Discussionmentioning
confidence: 92%
“…No significant correlations were found between the levels of airborne bacteria in outside air versus indoor air. This should not be surprising since there are few pathogenic bacteria found in outside air, with most being environmental bacteria that pose no hazard to humans (Lee et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing has an advantage over the conventional culture-based microbial identification method that neglects the important indoor microorganisms that develop a viable but non-cultivable state ( Muthuirulan and Sharma, 2017 ; Tong et al, 2017 ; Gao et al, 2018 ; He et al, 2020 ). The 16s amplicon sequencing method has been applied for bacterial community profiling from indoor aerosols ( Chen et al, 2017 ; Chakrawarti et al, 2020 ; Behbehani et al, 2021a ; Lee et al, 2021 ), particulate matter in the air ( Habibi et al, 2021e ), and dust ( Al Salameen et al, 2020 ; Li et al, 2021 ), among other matrixes. The targeted sequences of the internal transcribed spacer (ITS) region have also been sequenced to gain information on the fungal communities within air samples ( Okten and Asan, 2012 ; Al Salameen et al, 2020 ; Behbehani et al, 2021a , b ; Lee et al, 2021 ; Salameen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%